NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM RELIEF GARUDEYA DI CANDI SUKUH - Margiyono, Toto; Maharani, Hastin; Purwanto, Heri (Jawa Dwipa, 2024)
Sukuh Temple is one of the cultural heritage sites that has endured to the present day. The structure of Sukuh Temple features various relief carvings, one of which is the Garudeya relief, holding a significant religious role and function within spiritual life. The research problem is formulated around three research questions: the storyline depicted in the Garudeya relief, the meaning embedded within the Garudeya relief, and the values of Hindu religious education contained within it. The purpose of this research is to analyze, understand, and uncover the storyline, meanings, and educational values represented in the Garudeya relief. The findings of the research indicate that the Garudeya relief storyline is carved across five panels located on the first and third terraces of Sukuh Temple, illustrating the story of Garuda freeing his mother from enslavement. The Garudeya relief also carries profound meanings within the context of culture, spirituality, and history. The tale of Garuda reflects values such as sacrifice, perseverance, and bravery. Additionally, themes of devotion and filial piety (Guru Rupaka) are evident in Garuda’s efforts to liberate his mother from the shackles of bondage.